2011
DOI: 10.1097/dad.0b013e31820a2027
|View full text |Cite
|
Sign up to set email alerts
|

Sebaceous Carcinoma: An Immunohistochemical Reappraisal

Abstract: The rates of distant metastases and tumor death in sebaceous carcinoma (SC) have been reported to be higher than those of other cutaneous carcinomas, such as squamous cell carcinoma (SCC) and basal cell carcinoma (BCC), regardless of whether they occur in ocular or extraocular regions. Therefore, strict differentiation of SC from SCC and BCC is required. In this article, we report immunohistochemical findings of SC and compare these data to those of SCC, BCC, and sebaceoma. An immunohistochemical study was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
111
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(120 citation statements)
references
References 24 publications
9
111
0
Order By: Relevance
“…CD 10 is usually absent in SC, which helps in distinguishing it from BCC. Ansai et al [14] showed that positivity for adipophilin is most useful in the diagnosis of sebaceous neoplasms. Anti-AR (androgen receptor) is described as the best marker to differentiate between SC and SCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CD 10 is usually absent in SC, which helps in distinguishing it from BCC. Ansai et al [14] showed that positivity for adipophilin is most useful in the diagnosis of sebaceous neoplasms. Anti-AR (androgen receptor) is described as the best marker to differentiate between SC and SCC.…”
Section: Discussionmentioning
confidence: 99%
“…Differentiation between SC, squamous cell carcinoma (SCC) and basal cell carcinoma (BCC) has been shown to be difficult with routine staining methods [14]. As the treatment of SC differs from the treatment of SCC and BCC [15,16], discrimination remains important and special staining methods are recommended [9,14,17].…”
Section: Introductionmentioning
confidence: 99%
“…They also have been found in the adrenal gland and Leydig cells, as well as brown and white fat [59]. These markers are well-characterized in sebaceous skin and eye tumors, with 95-100% of skin and eyelid sebaceous tumors staining with these markers in three recent studies [58,60,61]. However, in the salivary gland, these markers have only been studied in the sebaceous variant of epithelial myoepithelial carcinoma and in one sebaceous carcinoma of the tongue [62,63].…”
Section: Differential Diagnosismentioning
confidence: 99%
“…Ansai et al 1 found that androgen receptor (AR) and adipophilin ( Figure 1) expression supports the diagnosis of sebaceous carcinoma, rather than SCC.…”
Section: Cutaneous Adnexal Neoplasms Sebaceous Neoplasmsmentioning
confidence: 99%
“…2,3 Reactivity for adipophilin in sebaceous tumors can also distinguish them from BCC. 1 The utility of Ber-EP4 in this setting is controversial; although BCCs stain positive for Ber-EP4, there is varying literature on its reactivity in sebaceous lesions. 2,4 Adipophilin is a protein on the surface of intracellular lipid droplets and thus shows expression in sebaceous lesions, particularly well-differentiated lesions.…”
Section: Cutaneous Adnexal Neoplasms Sebaceous Neoplasmsmentioning
confidence: 99%